Multimodal imaging of central retinal artery occlusion with retained cilioretinal perfusion - Walkden, Andrew (BMJ Case Rep, 2016)
A man aged 59 years old presented with sudden, painless, monocular visual loss due to central retinal artery occlusion. Central vision was retained and peripheral vision lost due to retained cilioretinal perfusion. Increased inner retinal thickening and reflectivity followed by subsequent reduction was documented by sequential imaging. This is the first report of such events monitored with spectral-domain optical coherence tomography where central visual acuity was maintained.